AN Analysis of the development of Russian industry ("Journal "U". Economy. Management. Finance.", 2022)
The article is devoted to the study of the development of Russian industry in the conditions of sanctions and import substitution. The purpose of the study is to analyze the development of Russian industry in difficult conditions of re-equipment and reconfiguration of production processes for import substitution. The dynamics of industrial production in various areas of production in the country and its regions is considered. The positive and negative dynamics of various economic indicators, including the production index, are revealed. Based on the conducted research, the general conclusion is formulated that effective industrial development is expedient for the country.
Keywords: Industry; industrial production; industrial production index; manufacturing industry; extractive industries